Faktor–Faktor Penyebab Keterlambatan Pada Pekerjaan Pile cap (Studi Kasus: Proyek Upgrade Trans Studio Mall Makassar) - Sulistiawati Marioga; Josefine Ernestine Latupeirissa; Meti (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
Pile cap as an important part used in construction engineering. Construction projects have a completion schedule, and pile caps as part of a construction project must not be delayed. The purpose of this study is to determine the factors that cause delays in Pile cap work. The analysis method to calculate the results of questionnaire distribution is simple correlation analysis. The results of this study indicate that there are seven factors causing delays Pile cap work on the Trans Studio Mall Makassar upgrade project, namely: (1) Lack of manpower, (2) Late delivery of materials, (3) Rainfall intensity factor, (4) Lack of labor expertise, (5) equipment shortage, (6) equipment damage, (7) the factor of the change of design by the owner. From the results of the calculation of the product moment correlation factor of the lack of labor with the Pearson correlation coefficient value of 0.821 has a very strong relationship.